2007
DOI: 10.1097/jom.0b013e31811eadd3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Effects of Changes in Psychosocial Work Characteristics: A Prospective Cohort Study

Abstract: These findings support a possible causal relationship between work characteristics and mental health and can be used for designing effective prevention and intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…As psychosocial work conditions also relate to the development of burnout,6 11 continuous assessment and improvement of work conditions are called for to extend individuals’ participation in the labour force. Studies have shown that change in working conditions can generate positive effects on decreasing levels of burnout,44 45 experienced fatigue,46 and even sickness absence 22…”
Section: Discussionmentioning
confidence: 99%
“…As psychosocial work conditions also relate to the development of burnout,6 11 continuous assessment and improvement of work conditions are called for to extend individuals’ participation in the labour force. Studies have shown that change in working conditions can generate positive effects on decreasing levels of burnout,44 45 experienced fatigue,46 and even sickness absence 22…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, no causal conclusions can be drawn. Existing longitudinal research within the field of occupational health tried to provide evidence for a causal relationship between characteristics of the work situation and mental health, thereby mainly focusing on the so-called normal causal relationship, i.e., how do characteristics of the work situation affect mental health over time [1,10]. The reversed relationship, i.e., how does mental health influence Journal of Psychosomatic Research 66 (2009) 137 -145 the work situation, has hardly been examined so far [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is complex and multidimensional and varies in intensity depending on the imposed overload [19]. Workplace fatigue is a common complaint that requires attention due to its high prevalence and its association with serious dysfunctions among workers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Workplace fatigue is a common complaint that requires attention due to its high prevalence and its association with serious dysfunctions among workers [5]. It affects physical and mental health [3, 9], increasing the chance of accidents and musculoskeletal complaints [10], and reducing performance and productivity [4]. …”
Section: Introductionmentioning
confidence: 99%